Os fundos financeiros e o agronegócio brasileiro: as vinculações globais entre as multinacionais e o capital financeiro - Oliveira, Alessandro Francisco Trindade de (2022)
The relationship created between the financial system and Brazilian agribusiness, in the last decades of the 20th century and in the first two of the 21st century, led to the development of this thesis, which is based on the study of the connections between financial funds and business corporations that operate in this productive segment within the Brazilian territory. The largest financial funds grew in the center of the capitalist system and became, in recent decades, gigantic complexes of speculative capital allocation, which began to seek fractions of productive capital that presented financial returns in the short and medium term in different parts of the world. In order to understand how the current articulation between the agribusiness and the financial system was arrived at, it was initially sought to understand how neoliberalism promoted by the central axis of global capitalism transformed and/or deregulated the capitalist production mode forged after the middle of the past century, in which economic planning and part of the productive investment were carried out jointly with the State. The analysis of the 1990s allowed us to understand that the extreme reliance on private capital reallocation mechanisms generated deficiencies in the national productive organization, with an advance of multinational companies through acquisitions that generated sectorial oligopolies and foreign technological dependence. The institutions and mechanisms of productive promotion that were extremely important for building the national productive apparatus lost strength in the late 1990s. BNDES and credit lines linked to government resources had their scope reduced, due to the emergence of private means of granting productive credit. Even between the years 2000-2015, when we had a brief moment of resumption of forms of planning and productive promotion in the alliance between public investments and the private sector, the confidence that the private sector should be the main inducer of investments was not left aside. At the present time, it is understood that financial funds are growing as one of the main instruments to move between real and financial assets, inserting themselves in the capital fractions through the financial market and using large companies as fixed capital in the territory, from so that it is no longer possible to talk about financialization without talking about the financial funds. The fact observed through the compositions of the largest shareholders in the large companies operating with the agribusiness was that the funds hold stakes in all large publicly traded companies, creating a ramification of stakes that allows a classification of the phenomenon as a large financial network, interconnected by information systems and which also allows for the ability to migrate capital between companies and also between countries and world financial centers. Thus, the central thesis defended is that financial funds represent a higher echelon of financialization, so that it is not possible to talk about financialization without highlighting the funds in the various productive segments, and therefore also in agribusiness.